Using Environmental DNA to Detect Whales and Dolphins in the New York Bight - Alter, S. Elizabeth; King, Carissa D.; Chou, Emily; Chin, Sam Chew; Rekdahl, Melinda; Rosenbaum, Howard C. (Frontiers in Conservation Science, 2022)
Determining how cetaceans and other threatened marine animals use coastal habitats is critical to the effective conservation of these species. Environmental DNA (eDNA) is an emerging tool that can potentially be used to detect cetaceans over broad spatial and temporal scales. In particular, eDNA may present a useful complementary method for monitoring their presence during visual surveys in nearshore areas, and for co-detecting prey. In conjunction with ongoing visual surveys, we tested the ability of eDNA metabarcoding to detect the presence and identity of cetaceans in the New York Bight (NYB), and to identify fish species (potential prey) present in the area. In almost all cases in which humpback whales and dolphins were visually observed, DNA from these species was also detected in water samples. To assess eDNA degradation over time, we took samples in the same location 15 and 30 minutes after a sighting in seven instances, and found that eDNA often, but not always, dropped to low levels after 30 minutes. Atlantic menhaden were detected in all samples and comprised the majority of fish sequences in most samples, in agreement with observations of large aggregations of this important prey species in the NYB. While additional data are needed to better understand how factors such as behavior and oceanographic conditions contribute to the longevity of eDNA signals, these results add to a growing body of work indicating that eDNA is a promising tool to complement visual and acoustic surveys of marine megafauna.